An assessment of the agri-food distribution services industry in CARICOM : final draft - Best, Robert ([Caribbean Regional Negotiating Machinery] [Christ Church]BB, 2006)
Defines the industry and seeks to understand the global food distribution sector for the purpose of establishing industry benchmarks and identifying trends and competitiveness improvement strategies. Assess the economic value of the sector to the region as well as other indicators of performance as a precursor to assessing the extent to which the sector is adopting appropriate international competitiveness strategies.